2017
DOI: 10.1371/journal.pone.0187137
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based Brain Healthcare Quotients: A bridge between neural and behavioral analyses for keeping the brain healthy

Abstract: Neurological and psychiatric disorders are a burden on social and economic resources. Therefore, maintaining brain health and preventing these disorders are important. While the physiological functions of the brain are well studied, few studies have focused on keeping the brain healthy from a neuroscientific viewpoint. We propose a magnetic resonance imaging (MRI)-based quotient for monitoring brain health, the Brain Healthcare Quotient (BHQ), which is based on the volume of gray matter (GM) and the fractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 43 publications
2
68
1
Order By: Relevance
“…The robust significance of the BGE suggests that this new coefficient is a good candidate for FC-BHQ and is at least comparable to the already-proposed FA-BHQ (Nemoto et al, 2017), in which the reported R was −0.417. Although further refinement will enable more accurate representation of the age-related modulation of FC among individual subjects, the BGE provides important descriptions about the patterns of regional differences and the implications of GE, in particular, information transferability.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The robust significance of the BGE suggests that this new coefficient is a good candidate for FC-BHQ and is at least comparable to the already-proposed FA-BHQ (Nemoto et al, 2017), in which the reported R was −0.417. Although further refinement will enable more accurate representation of the age-related modulation of FC among individual subjects, the BGE provides important descriptions about the patterns of regional differences and the implications of GE, in particular, information transferability.…”
Section: Discussionsupporting
confidence: 59%
“…However, despite the informativeness of age-related GE, proposing a quotient based on whole-brain FC remains an open question, although grey matter volume or fractional anisotropy have been used as sources for computing the Brain Healthcare Quotient (BHQ; Nemoto et al, 2017). In this article, we broaden the scope of monitoring brain health by incorporating functional connectivity into this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this trial, healthy, middle-to-older aged adults were treated with a beverage containing IAAs (3 mg/190 mL) for 4 weeks. A recently-developed assay of brain function based on magnetic resonance imaging (MRI) called the Brain Healthcare Quotient (BHQ) based on gray matter volume (GM-BHQ) [43], was significantly improved after the intervention compared to baseline. This preliminary data suggested that IAA treatment effectively modulated human brain activity.…”
Section: Iaas Enhance Cognitive Function Via Activation Of the Vagus mentioning
confidence: 99%
“…Lastly, using Johns Hopkins University (JHU) DTI-based white-matter atlases 63 , regional FA quotients were extracted and averaged across regions to produce participant-specific FA-BHQs. For more details, please see Nemoto et al 64 . psychological scales.…”
Section: Mri Data Acquisitionmentioning
confidence: 99%